Phenotypic and Genotypic Detection of Staphylococcus aureus and Escherichia coli in Subclinical Mastitis Goat Milk in Lumajang, Indonesia - Khasanah, Himmatul; Putra, Nalendra Gigih Wibawanto; Hariyadi, Nanang Tri; Widodo, Nur; Widianingrum, Desy; Yulianto, Roni; Cruz, Joseph F. Dela; Pratiwi, Nurul (Jurnal Medik Veteriner, 2025)
This study aimed to identify the Staphylococcus aureus and Escherichia coli bacteria that cause subclinical mastitis in dairy goats in the Senduro sub-district of Lumajang regency, Indonesia. A total of 116 milk samples from 58 dairy goats were tested for the California Mastitis Test (CMT). CMT-positive samples were used for bacterial identification through phenotypic and genotypic analyses. Phenotypic analysis was conducted by culturing bacteria on natrium agar media and followed in selective media. The genotypic analysis employed a specific primer of S. aureus using the 23SrRNA gene and E. coli using the 16SrRNA gene as confirmation of the gold standart. The results of this study showed positive subclinical mastitis in dairy goat samples, which consisted of 21 samples of CMT 1 and a sample of CMT 2. Bacterial identification with phenotypic assays documented 16 samples having S. aureus and one sample having E. coli. The validated genotypic assays showed from 16 samples, validated 5 samples of S. aureus infection and one E. coli infection. In conclusion, bacterial identification of S. aureus and E. coli predominantly infects the SCM dairy goats in the Senduro sub-district as evidenced by the phenotypic analysis and followed by genotypic using the PCR method.